Border Mythogenesis - Nsiangani, Kibavuidi; Pius Mulaba Lumpungu; Holenu Mangenda (USK Journal of Political Science and Epistemology, 2023)
Colonial borders are not only lines on maps. They are jurisdictions that distribute protection, movement, land access, and political voice. When state capacity is uneven and historical literacy is thin, border disputes become ignitable through narrative operations that convert ambiguity into mobilizable certainty, often accelerating coercion or proxy violence. This paper models that ignition pathway as Border Mythogenesis (BM): a codeable set of claim motifs (restoration, priority, othering, delegitimation, and security laundering) that predictably intensify under specific conditions. To remain consistent with prior work, we treat these motifs as a domain expression of the Entitlement Cascade and its allied selection dynamics (ISM/PDI): when beneficiary systems face accountability stress or perceived loss of dominance, they frequently deploy portable entitlement scripts (priority claims, credit seizure, universalization, and victim inversion). We refer to this operational motif family as Colonial Entitlement Rhetoric (CER), not as a separate theory but as a measurable surface form of the same cascade logic across border disputes and privilege‑defense contexts. CER does not replace material drivers such as resources, security fragmentation, or elite rent capture. It functions as an accelerant that lowers moral cost and raises mobilisation capacity, and it becomes most visible under credible weakness signals. Methodologically, we provide preregisterable codebooks, low‑tech replication protocols using public sources (official speeches, parliamentary records, broadcaster transcripts, archived newspapers), and a worked empirical pilot template with falsification conditions. The paper closes with circuit‑breaker recommendations for heritage institutions, educators, and civic actors that increase epistemic thickness, expand non‑violent pathways for boundary settlement, and reduce the conversion of narrative spikes into coercion.
Colonial Borders as Risk Surfaces, Narrative Weapons, and Proxy Conflict Triggers in Pan‑African Futures (1884–2023)